Inter-Institutional Comparison on Working Power Loss Evaluated Cases - Ünal, Volkan; Baklacıoğlu, Ferruh; Ünal, Esra Özgün; Çetinkaya, Zafer; Demir, Muhammet; Çağdır, Ahmet Sadi (The Bulletin of Legal Medicine, 2016)
Objective: In Turkey, individuals who want to retire due to illness and determined within the provisions of the relevant rules and regulations are defined as 'retirement due to disability1. When the insured apply with a petition, describing that s/he cannot work because of the diseases, retirement process begins. First Social Security Institution in case of objection Social Security Supreme Council of Health prepares reports about individuals. Third Specialization Board of the Council of Forensic Medicine is the final expertise authority on these cases. With this study it is aimed to reveal the decision differences on 'retirement due to disability1 cases between the Third Specialization Board of the Council of Forensic Medicine and the other institutions and, guided with the findings, to provide the standardization in practical implementation.Materials and Methods: For this study; the reports of the 3rd Specialization Board of The Council of Forensic Medicine were retrospectively investigated and the cases who were reported as not suitable for the retirement due to diseases by Social Security Institution and Social Security Supreme Council of Health but reported as suitable for the retirement due to diseases by the 3”1 Specialization Board were included.Results: Totally sixty four cases were determined. Fifty seven of the cases were male and seven ofthem were female. Average age of female cases was 50.71, male cases were 49.89 and average age of all cases was 49.98.Conclusion: Even the rules and regulations are same, there are differences between institutions. While rules and regulations are constituted, taking common decisions by negotiating on practice principles should reduce the differences between institutions and provide faster decision makings. Institutions should arrange routine meetings and discuss about the cases and present assessments interactively.Keywords: Working Power Loss, Inter-Instutional Comparison, Forensic medicine.
Keywords: working power loss; inter-instutional comparison; forensic medicine